Proposed new standard of procedures (SOPs) for announcement in New IIUM/KAED website - Yaali, Syarel Azill; Ayob, Mohd Fairullazi (2018)
Announcement from Department Representative: SOP: Announcement of news / event to IIUM Website / KAED Website SOP: Announcement of News / Event for E-Announcement (i.e. IIUM Billboard and Emails). Announcement from Students Representative: SOP: Announcement of news / event to IIUM Website / KAED Website. SOP: Announcement of News / Event for E-Announcement (i.e. IIUM Billboard and Emails).